Analysis of Marketing Strategies in Collaboration between HEYTEA and Otome Games - Jin, Zixuan (Transactions on Social Science, Education and Humanities Research, 2024)
In today's fiercely competitive market environment, brand collaboration has become an important strategy to attract consumer attention. HEYTEA and Otome Games, as leading brands in their respective fields, have successfully conducted joint marketing activities, bringing more attention and recognition to both parties. This paper analyzes and compares the joint marketing strategies of HEYTEA and Otome Games to explore the reasons for their success and the implementation effects of marketing strategies. The analysis focuses on the joint marketing strategy of HEYTEA, a Chinese tea brand, and Otome Games, targeting a specific audience and its impact on them. It begins with an introduction to the brand backgrounds of HEYTEA and Otome Games, followed by an analysis of their product and brand culture, joint marketing strategies, and their significance and impact. Through the analysis of this study, it can be found that joint marketing is an effective brand promotion strategy that can enhance brand influence and competitiveness. Meanwhile, when brands choose joint cooperation partners and design joint products, they need to fully consider the needs of the target audience and the consistency of brand image to achieve better marketing results.